Analisis Harga Pokok Pesanan Terhadap Penentuan Harga Pokok Produksi dengan Metode Variabel Costing pada Pt. Makmur - Delfia Uli Damayanti Siagian; Anik Nurmawati; Merina Tinta Fatrissia; Syifa Amelia; Sabrina Octaviani (Jurnal Mutiara Ilmu Akuntansi, 2025)
This study analyzes the application of the order costing method with a variable costing approach at PT Makmur, a manufacturing company engaged in the beverage cup industry. Accurate determination of the cost of goods manufactured is crucial to support strategic decision making, profit optimization, and management of company resources. This research uses a literature study method with a qualitative approach to explore in-depth understanding related to the calculation of production costs. The results of the analysis show that the variable costing method provides benefits in identifying contribution margins and controlling variable costs, while the full costing method tends to produce a more comprehensive estimate of production costs by including fixed costs. The findings indicate a significant difference in net profit between the two methods, which has an impact on selling pricing decisions and production strategies. The implication of this study is that it provides practical guidance for PT Makmur and similar companies to choose a costing method that suits financial and operational objectives, and improve competitiveness through more efficient cost management.